2002
DOI: 10.1542/peds.109.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Controlled Trial Comparing Surfaxin (Lucinactant) Lavage With Standard Care for Treatment of Meconium Aspiration Syndrome

Abstract: Dilute Surfaxin lavage seems to be a safe and potentially effective therapy in the treatment of MAS. Data from this investigation support future prospective, controlled clinical trials of bronchoalveolar lavage with Surfaxin in neonates with MAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
13

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(113 citation statements)
references
References 26 publications
6
94
0
13
Order By: Relevance
“…In addition, there are two studies evaluating the use of surfactant lavage in newborn infants with MAS. Although, the techniques used in these studies were different, both the studies reported promising results [18,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are two studies evaluating the use of surfactant lavage in newborn infants with MAS. Although, the techniques used in these studies were different, both the studies reported promising results [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Despite prophylactic oropharyngeal suctioning of infants delivered with meconiumstained amniotic fluid, the incidence of MAS varies widely (1.7%-35.8%) [5,33,37]. In its severest form, MAS results in a vicious cycle of hypoxemia, hypercapnia, acidosis, and death [1,5,29].…”
Section: Introductionmentioning
confidence: 99%
“…No adverse effects were reported. In a multicenter study, Wiswell et al 42 examined the use of surfactant lavage for MAS using lucinactant, a synthetic surfactant. Although it was potentially safe and effective, lucinactant failed to show a significant advantage with surfactant lavage.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
“…Another peptide design strategy has used the Leu-Leu repeat sequence in the C-terminal helical region of SP-B (residues 57-63) as a molecular template for the synthetic peptide KL 4 (Surfaxin) (36). This peptide does not have the in Vitro and in ViVo efficacy observed for native and synthetic SP-B sequences (37) but has shown some promise as a bronchoalveolar lavage for improving lung function in meconium aspiration syndrome (38).…”
mentioning
confidence: 99%